PENGEMBANGAN MODEL BIMBINGAN KONSELING KRISTEN UNTUK MENINGKATKAN KECERDASAN EMOSIONAL SISWA - Glodia Angel; Tiara Rongre Lebang, Gina Miranda, Mersi Pondi', Hermin Banna’ (CV. ADIBA AISHA AMIRA, 2025)
This study aims to develop a Christian counseling guidance model aimed at enhancing students' emotional intelligence. Emotional intelligence has been recognized as a crucial factor in students' personal and academic success, and the Christian counseling guidance approach can significantly contribute to the holistic development of this aspect. In this study, a model is developed based on the principles of Christian theology and relevant counseling theories, with the goal of providing a solid foundation for enhancing students' emotional well-being. The research methods used include literature review, theological studies, as well as model testing and evaluation through qualitative approaches. The research findings indicate that the developed Christian counseling guidance model has great potential in strengthening students' emotional skills, improving interpersonal relationships, and enriching their spiritual dimension. The practical implications of this research lie in providing a comprehensive and meaningful framework for Christian counseling practitioners in guiding students towards balanced holistic growth. It is hoped that this research will make a valuable contribution to enriching the practice of Christian counseling guidance and enhancing students' overall quality of life.